Determination of Iron (Fe) and Calcium (Ca) in NIST SRM 1566b (Oyster tissue) using Flame Atomic Absorption Spectrometry (F-AAS) by Standard Addition Method - Fitri Dara; Y Susanto Ridwan (Syarif Hidayatullah State Islamic University, 2011)
NIST Standard Reference Material (SRM 1566b) was employed for the determination of Iron (Fe) andCalcium (Ca) as nutrients in food matrix using Flame Atomic Absorption Spectrometry (F-AAS). Thecertified value of SRM 1566b for Fe and Ca are 205.8 ± 6.8 mg/kg and 0.0838 ± 0.0020 (%) or 838 ±20 mg/kg, respectively. This certified values are based on results obtained by single primary method(Isotope Dilution Inductively Couple Plasma Mass Spectrometry) at NIST with confirmation by othermethods at National Metrology Institute of P.R. China. This paper proposed a method fordetermination of Fe and Ca in food matrix as recommended by AOAC official with a littlemodification. The method was commenced from the destruction of all organic matter by dry oxidationbefore analysis by standard addition. Under optimum condition, the results of the determination of Feand Ca in SRM 1566b were agreed well with the certificate value. This method would be useful forroutine analysis in food testing laboratories.